2021
DOI: 10.1038/s41598-021-02637-w
|View full text |Cite
|
Sign up to set email alerts
|

Local delivery of hydrogel encapsulated vascular endothelial growth factor for the prevention of medication-related osteonecrosis of the jaw

Abstract: The anti-angiogenic effects of bisphosphonates have been hypothesized as one of the major etiologic factors in the development of medication-related osteonecrosis of the jaw (MRONJ), a severe debilitating condition with limited treatment options. This study evaluated the potential of a gelatine-hyaluronic acid hydrogel loaded with the angiogenic growth factor, vascular endothelial growth factor (VEGF), as a local delivery system to aid in maintaining vascularization in a bisphosphonate-treated (Zoledronic Acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 77 publications
0
6
1
Order By: Relevance
“…It is widely believed that BPs have antiangiogenic properties and suppress VEGF production via apoptosis [ 18 , 19 ]. NBPs such as ZA directly inhibit angiogenesis in vitro and in vivo, reducing vascularity in MRONJ lesions and quantitatively decreasing microvessels during early bone healing stages [ 5 , 6 , 13 , 20 , 21 ]. Furthermore, angiogenesis in post-extraction socket healing is inhibited by BPs, and both BPs and denosumab led to decreased arterial area, venous area, and overall vascularity in periodontal tissues during early and late MRONJ development [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely believed that BPs have antiangiogenic properties and suppress VEGF production via apoptosis [ 18 , 19 ]. NBPs such as ZA directly inhibit angiogenesis in vitro and in vivo, reducing vascularity in MRONJ lesions and quantitatively decreasing microvessels during early bone healing stages [ 5 , 6 , 13 , 20 , 21 ]. Furthermore, angiogenesis in post-extraction socket healing is inhibited by BPs, and both BPs and denosumab led to decreased arterial area, venous area, and overall vascularity in periodontal tissues during early and late MRONJ development [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted by Sharma et al (2021) on the effect of local delivery of hydrogel encapsulated VEGF for the prevention of medication-related osteonecrosis of the jaw has been investigated. They concluded that the application of locally delivered VEGF into the extraction sockets might induce bone healing and prevent MRONJ via a pro-angiogenic and immunomodulatory mechanism [ 13 ]. In general, the main aim of these studies was preventing MRONJ via a neoangiogenesis mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Altered VEGF expression was observed after treatment with BPs, possibly related to TGF-β expression 44. To tackle this characteristic, a novel research by Sharma et al,45 evaluated the use of a gelatin-hyaluronic acid hydrogel bound with the VEGF, to sustain vascularization after tooth extraction in an animal model under Zoledronic Acid treatment. Results showed that total osteonecrosis and inflammatory infiltrate was significantly reduced in the presence of VEGF and neovascularization was significantly improved preventing MRONJ via a proangiogenic and immunomodulatory mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Bisphosphonates, with their extensive biological half-life and strong affinity for bone hydroxyapatite, can incite apoptosis via farnesyl diphosphate synthase inhibition within the mevalonate pathway 4 . These agents contribute to MRONJ through dual actions: disrupting bone cell activities-specifically osteocytes, osteoclasts, and osteoblasts-and impeding angiogenesis, with systemic vascular implications 5 . Clinically, bisphosphonates bolster bone density and minimize fractures in osteoporosis, also addressing pain and hypercalcemia in bone metastases-related cancer treatments 5 .…”
Section: Bisphosphonate Pharmacodynamics and Mronj Pathogenesismentioning
confidence: 99%
“…These agents contribute to MRONJ through dual actions: disrupting bone cell activities-specifically osteocytes, osteoclasts, and osteoblasts-and impeding angiogenesis, with systemic vascular implications 5 . Clinically, bisphosphonates bolster bone density and minimize fractures in osteoporosis, also addressing pain and hypercalcemia in bone metastases-related cancer treatments 5 . Figure 1(a) 0.2 Denosumab's Mechanism and Its MRONJ Risk Profile Denosumab, a targeted monoclonal antibody, impedes receptor activator of NF-kB ligand (RANKL), a molecule essential to osteoclast development and survival-a significant step in bone disorder therapeutics 4 .…”
Section: Bisphosphonate Pharmacodynamics and Mronj Pathogenesismentioning
confidence: 99%